2018
DOI: 10.2147/dddt.s174058
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV represses high glucose-induced mesangial cells activation by enhancing autophagy via SIRT1 deacetylation of NF-κB P65 subunit

Abstract: AimMesangial cell (MC) activation plays an important role in many glomerular diseases associated with renal fibrosis, including diabetic kidney disease (DKD). The aim of this study was to determine whether Astragaloside IV (AS-IV) modulated MC activation in DKD via autophagy by specifically regulating the autophagy inducer sirtuin 1 (SIRT1).MethodsCultured MCs and diabetic KK-Ay mice were treated with AS-IV, and the markers and regulatory mediators of autophagy were analyzed using Western blotting, real-time P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 31 publications
(40 reference statements)
2
42
0
Order By: Relevance
“…Emerging studies have shown that metformin can improve the blood glucose levels of DM patients through activating AMP‐activated protein kinase (AMPK), which also activates SIRT1 and regulates energy metabolism through FOXO1 . Wang et al revealed that although high glucose reduces the SIRT1 level and increases inflammatory factor expression in mesangial cells, SIRT1 activation downregulates the transcriptional activity of nuclear factor‐kappaB (NF‐κB) and inhibits inflammatory factor production and improves the inflammatory response in the kidney …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging studies have shown that metformin can improve the blood glucose levels of DM patients through activating AMP‐activated protein kinase (AMPK), which also activates SIRT1 and regulates energy metabolism through FOXO1 . Wang et al revealed that although high glucose reduces the SIRT1 level and increases inflammatory factor expression in mesangial cells, SIRT1 activation downregulates the transcriptional activity of nuclear factor‐kappaB (NF‐κB) and inhibits inflammatory factor production and improves the inflammatory response in the kidney …”
Section: Introductionmentioning
confidence: 99%
“…14 Wang et al 15 revealed that although high glucose reduces the SIRT1 level and increases inflammatory factor expression in mesangial cells, SIRT1 activation downregulates the transcriptional activity of nuclear factor-kappaB (NF-κB) and inhibits inflammatory factor production and improves the inflammatory response in the kidney. 15 The present work explores the role of metformin in mesangial cell proliferation, inflammation and ECM accumulation induced by high glucose and elucidates the underlying mechanism of metformin function on SIRT1/FOXO1-mediated autophagy to provide new insight into the development of DN.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations of TLRs play a potent role in susceptibility to AD [22]. AS-IV presented a wide range of pharmacological effects through multiple pathways, however, most of them are related to TLR4-mediated NF-κB signalling pathways [8][9][10]. Therefore, we assessed several TLRs gene expression of epithelium in remission phase of AD-Re, and evaluated the effects of AS-IV on TLRs expression.…”
Section: Discussionmentioning
confidence: 99%
“…Astragaloside IV (AS-IV), a natural saponin abundant in Astragalus membranaceus, possesses multiple pharmacological effects including anti-inflammatory, anti-fibrotic, anti-tumor, neuronal and cardiac protection effects via numerous signaling pathways [3][4][5][6][7]. Accumulated evidence recently points to the important role of AS-IV in regulating Toll-like receptors (TLRs)-mediated NF-κB pathway to exert its pharmacological effects [8][9][10]. Yu-Ping-Feng-San (YPFS), a well-known traditional Chinese medicine (TCM), is clinically applied for allergic disorders with reduced relapse rates and recurring severity [11,12].…”
mentioning
confidence: 99%
“…Aside from the SIRT1‐mediated inhibition of NF‐κB activity, NF‐κB signaling is also able to suppress SIRT1 activity through the expression of miRNAs as well as through an increase in ROS production . These antagonistic functions of NF‐κB and SIRT1 play several roles in inflammation and metabolism, regulation of autophagy, and neuroinflammation and cognitive impairment induced by sepsis . Therefore, the outcome of crosstalk between SIRT1, ROS, and NF‐κB should be decoded in the tumor context.…”
Section: Introductionmentioning
confidence: 99%